Multilayered Films Fabricated from Combinations of Degradable Polyamines: Tunable Erosion and Release of Anionic Polyelectrolytes - Zhang, Jingtao (2006)
This investigation sought to develop methods that permit broad and tunable control over the erosion of multilayered polyelectrolyte assemblies and the release of anionic polymers in physiologically relevant media. We report the fabrication and characterization of multilayered films ~60 nm thick using sodium poly(styrene sulfonate) (SPS) and different combinations of three different hydrolytically degradable polyamines (1–3). We investigated two different approaches to film fabrication: 1) fabrication using solutions comprised of defined mixtures of two different polyamines, and 2) fabrication of films composed of different numbers of layers of two different polyamines. In general, films fabricated using polyamine solutions composed of defined mixtures of two different polyamines had erosion and release profiles that were dictated almost entirely by the most hydrophobic polyamine used to fabricate the films. In contrast, the fabrication of films having different numbers of layers of different polyamines permitted broad and tunable control over film erosion and the release of SPS. For example, films having the architecture (1/SPS)(n)(2/SPS)(m) released SPS with profiles that were intermediate to those of films fabricated exclusively from polymer 1 or polymer 2. Further, we demonstrated that it is possible to exert systematic control over the release of SPS by varying the relative numbers of layers of (1/SPS) or (2/SPS) incorporated into the films. The approaches reported here provide tunable control over the rate of the release of anionic polymers from surfaces coated with ultrathin multilayered films. This work could, with further development, contribute to the design of ultrathin films that permit tunable control over the release and delivery of therapeutically relevant macromolecules, such as proteins or DNA, from surfaces.